Post-Traumatic brain injury (TBI) presenting with Guillain-Barre syndrome and elevated anti-ganglioside antibodies: a case report and review of the literature. (3rd July 2015) - Carr, Kevin R.; Shah, Manan; Garvin, Rachel; Shakir, Ahmed; Jackson, Carlayne
Abstract : Guillain-Barré Syndrome (GBS) is a demyelinating polyneuropathy resulting in sensory, motor and autonomic symptoms. The severity of the disease can range from mild to severe but it is classically described as an ascending demyelinating process. Initially thought to be the sequelae of a bacterial or viral infection, the clinical symptoms of post-infective GBS can present up to 4 weeks after sentinel injury. A rarely defined post-surgical GBS has been since described after major cranial, cardiothoracic and gastro-intestinal surgery. Post traumatic GBS is an even more unusual presentation with very few cases reported in contemporary academic literature. We present a case of GBS presenting two weeks after non-operative traumatic brain injury (TBI) and a review of the literature.